PHYTOSSOCIOLOGICAL ASSESSMENT OF A NATURAL REGENERATION SITE IN THE SOUTHEAST ATLANTIC FOREST BIOME - Luís Gustavo de Paula Silva; Soraya Alvarenga Botelho; Klécia Gili Massi; Marivaldo Garcia Martins; Tharcísio Pelosato Nogueira; Jaurés Barbosa Guisard; Rodrigo Leite Marco Santos; Jordano Roma Buzati; Rodrigo Dametto; João Marcos Paiva; Ádila Hanna Justiniana Rodrigues; Natan Rodrigues Ferreira de Melo e Silva; et al. (Revista do Instituto Florestal, 2021)
On some portions of the biodiversity Atlantic Forest bioversity hotspot, land abandonment has regenerated back to forest. However, the composition and structure of these areas are not well known. Thus, the aim of this study was to inventory a 45 years old natural regeneration forest site in a small farm (68 ha) in the Southeast portion of Atlantic Forest Biome in Brazil. In November 2019 all regenerating individuals (<15 cm of circumference at ground level and> 50 cm of height) and adults (>15 cm of circumference at breast height) were counted, identified, classified in ecological groups, dispersal and conservation status, and measured in 0.34 ha. We calculated Importance Value (VI) for all species. Of the 2720 individuals sampled, 435 were adults and 2285 regenerating individuals. Families with greatest species richness were Fabaceae, Myrtaceae and Euphorbiaceae. The majority of species and individuals were non-pioneer and zoochorous. Most of the regenerants belong to the specie Guarea kunthiana and were non-pioneer species, wich might indicate an advanced stage of forest succession. Additionally, high VI species were mostly non-pionners.